2012
DOI: 10.1093/intimm/dxs098
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 is a novel regulator of human B-cell activation

Abstract: The outcome of the adaptive immune response is determined by the integration of both positive and negative signals, respectively, induced upon the triggering of co-signaling receptors. One of them, programmed cell death 1 (PDCD1/PD-1) has largely been shown to be involved in the negative regulation of T-cell activation. However, PD-1 is also expressed on human B cells, and its role(s) in the process of human B-cell activation remains uncertain thus far. In this study, we describe the expression of PD-1 on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
239
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(255 citation statements)
references
References 42 publications
10
239
2
4
Order By: Relevance
“…More precisely, we observed that blockade of TLR4 activation effectively abolished the primary HCC-SN-mediated induction of PD-1 + /hi B cells. This fi nding agrees with that of recent studies showing that activation of TLR by microbial products led to upregulation of PD-1 on monocytes and B cells ( 10,12 ). Notably, the TLR signals, particularly TLR9-CpG ODN interaction, also play an essential role in the terminal differentiation of B cells into plasma cells ( 31 ), but this process requires BCR engagement and costimulation via CD40L ( 32 ).…”
Section: Pd-1supporting
confidence: 91%
See 1 more Smart Citation
“…More precisely, we observed that blockade of TLR4 activation effectively abolished the primary HCC-SN-mediated induction of PD-1 + /hi B cells. This fi nding agrees with that of recent studies showing that activation of TLR by microbial products led to upregulation of PD-1 on monocytes and B cells ( 10,12 ). Notably, the TLR signals, particularly TLR9-CpG ODN interaction, also play an essential role in the terminal differentiation of B cells into plasma cells ( 31 ), but this process requires BCR engagement and costimulation via CD40L ( 32 ).…”
Section: Pd-1supporting
confidence: 91%
“…Blocking the interaction between PD-1 and PD-L1 can restore T-cell function and result in tumor regression in both humans and mice (6)(7)(8)(9). Nevertheless, it should be emphasized that, in addition to being expressed on exhausted T cells, PD-1 can be rapidly upregulated on B cells, natural killer T cells, monocytes, and dendritic cells in infl amed tissues (10)(11)(12)(13), suggesting that PD-1-associated cancer therapy targets not only T cells but also the whole immune system. Thus, evaluating PD-1 expression and function in non-T-cell leukocyte infi ltrate is essential for understanding the roles and potential suppressive mechanisms of PD-1 in tumor immunopathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…After transplantation, Th1, Th17 and the high level of IL-17, TNF-a and IFN-c in the periodontitis tissue can increase the expression of PD-L1 on MSCs, which inhibits the differentiation of B cells via PD-1 /PD-L1 pathway [45]. All MSCs were uniformly positive for HLA-ABC and lacked the expression of HLA-DR and the costimulatory molecules (e.g., CD40, CD80, CD86, CD134, and CD252) required for full T-cell activation [46], and in our previous study we showed that hPDLSCs displayed low immunogenicity [18]. However, after transplantation, a small amount of allogeneic PDLSCs might be presented to B cells as antigen by antigen-presenting cells, and these B cells might be stimulated and express IL-6 and B7, which activated the PD-1/PD-L1 expression of MSCs in periodontal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Today, although the inhibitory role of PD-1 in activated T cells has been widely studied, a few information is available on its triggering on human B cell surface. 28 Recently, Thibult et al 34 were first to report PD-1 expression by human B lymphocytes that could negatively regulate their activation, proliferation and IL-6 production. To date, the putative roles of B lymphocytes in generating a specific pre-metastatic microenvironment in the SLN¡ is also not well documented.…”
mentioning
confidence: 99%